1969
DOI: 10.1243/pime_conf_1969_184_086_02
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Vertical Flow Maps

Abstract: In this paper a vertical downward flow map and a vertical upward flow map are presented. A comparison of the two flow maps shows that significant differences exist between the two directions of flow. The experimental work was performed with an air-water flow in a 11/2-in inside diameter transparent tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1
4

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 4 publications
3
8
1
4
Order By: Relevance
“…This result was confirmed by Chakrabati (1976) in a horizontal 180° bend, Anderson and Hills (1974) in an inverted U, Kooijman and Lacey (1968) and Maddock et al (1974) in 60 o to 90 o bends at the top of a vertical pipe. locations is justified by the conclusions drawn by Golan and Stenning (1969). They reported that the effect of the bend on phase distribution disappeared by 10 D downstream of the end of the bend for the inverted U-bend case.…”
Section: Two-phase Film Thickness Distribution In 180 O Bendssupporting
confidence: 53%
See 2 more Smart Citations
“…This result was confirmed by Chakrabati (1976) in a horizontal 180° bend, Anderson and Hills (1974) in an inverted U, Kooijman and Lacey (1968) and Maddock et al (1974) in 60 o to 90 o bends at the top of a vertical pipe. locations is justified by the conclusions drawn by Golan and Stenning (1969). They reported that the effect of the bend on phase distribution disappeared by 10 D downstream of the end of the bend for the inverted U-bend case.…”
Section: Two-phase Film Thickness Distribution In 180 O Bendssupporting
confidence: 53%
“…Here, we focus on inverted U bends for which papers have been written by Golan and Stenning (1969), Hills (1973), Anderson and Hills (1974), Usui et al (1983), Hoang and Davies (1984), Takemura et al (1986). Golan and Stenning (1969) and Takemura et al (1986) who noted that they act as phase separators because of the combined effect of centrifugal forces and gravity. In a U bend the two forces act in the same direction, usually sending the liquid to the outside of the bend and gas to the inside.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be estimated using theoretical flow regime maps (Barnea, 1987) or experimental ones (Baker, 1954;Hewitt and Roberts, 1969;Golan and Stenning, 1969). Theoretical maps have the advantage of not being limited by experimental parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Golan e Stenning [59] observaram os padrões num tubo do tipo em U invertido consistido por um riser vertical seguido por um tubo descendente vertical. Martin [60] estudou a transição do padrão de escoamento em bolhas para o golfadas (slug flow) numa configuração vertical descendente, assim como foi estudado por Spedding e Nguyen [33].…”
Section: Escoamento Descendenteunclassified